A Cofacially Stacked Electron‐Deficient Small Molecule with a High Electron Mobility of over 10 cm2 V−1 s−1 in Air. (26th October 2015) - Dou, Jin‐Hu; Zheng, Yu‐Qing; Yao, Ze‐Fan; Lei, Ting; Shen, Xingxing; Luo, Xu‐Yi; Yu, Zhi‐Ao; Zhang, Shi‐Ding; Han, Guangchao; Wang, Zhi; Yi, Yuanping; Wang, Jie‐Yu; et al.
Abstract : A strong, electron‐deficient small molecule, F4 ‐BDOPV, has a lowest unoccupied molecular orbital (LUMO) level down to ‐4.44 eV and exhibits cofacial packing in single crystals. These features provide F4 ‐BDOPV with good ambient stability and large charge‐transfer integrals for electrons, leading to a high electron mobility of up to 12.6 cm 2 V −1 s −1 in air.